THE PHENOMENON OF AMBIGUITY IN ONLINE NEWSPAPER HEADLINES ON KOMPAS.COM - Muhammad Rikzan Maulana; Firdasari Desfiani; Najma Syauqi Chafid; Nailatul Mafazah; Redika Cindra Reranta (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2026)
This study aims to identify and analyze the phenomenon of grammatical ambiguity in the headlines of the online newspaper Kompas.com. Ambiguity in news headlines has become an interesting phenomenon in the digital era because it can affect readers' understanding of the information conveyed. This study uses a qualitative approach with a descriptive method to analyze 10 news headlines from Kompas.com from October 2 to November 2, 2025. Data collection techniques use the observation method with note-taking, while data analysis refers to the concept of syntactic-level grammatical ambiguity, including phrase, clause, and sentence structures. The results of the study show that grammatical ambiguity in Kompas.com headlines appears in various forms, including unclear subject-object-predicate relationships, uncertain word references, the absence of relational markers, and dense sentence structures without conjunctions. These findings indicate that although Kompas.com is a highly credible media outlet, the phenomenon of ambiguity still occurs due to the pressure to create headlines that capture readers' attention. This study contributes to the field of applied linguistics, particularly media discourse analysis, and can serve as a reference for journalism practitioners in crafting effective news headlines without sacrificing clarity of meaning.